Case report: Meningitis: a cause of reversible cerebral vasoconstriction syndrome? - Oukhai, Fida; Domigo, Valérie; Benzakoun, Joseph; Wolff, Michel; Ducros, Anne; Mas, Jean-Louis; Calvet, David (Frontiers in Neurology, 2023)
Introduction: Reversible cerebral vasoconstriction syndrome (RCVS) is characterized by thunderclap headache and reversible cerebral arteries vasoconstriction. Pathophysiology remains unclear but many triggers were reported. Case reports: We report 2 cases of patients with meningitis who developed RCVS confirmed by brain imaging. They presented clinical and CSF features of meningitis suspected to be infectious but no agent was identified. Headache and artery irregularities resolved with the improvement of CSF. Conclusion: These cases suggest that, in a context of meningitis, modification or atypical headaches should lead to brain imaging to rule out RCVS. We hypothesized that CSF inflammation may trigger cerebral arteries vasoconstriction